Potential Bioactivity of Carrot (daucus carota L) as a Health Protector Through Antioxidant, Antibacterial, and Antifungal Activities - Digna Renny Panduwati; Dian Pratiwi; Liza Mutia; Suryani MF Situmeang; Karolina Br Surbakti; Wardati Humaira; Sahala Fransiskus Marbun (Jurnal Penelitian Pendidikan IPA, 2025)
Carrots are one of the most popular plants in Indonesia. In addition to being a plant with a flavor favored, carrots also contain various bioactivities that can be utilized for health. This study aims to investigate the bioactivity of carrot extract, which includes antioxidant, antibacterial, and antifungal. The method used in this study is DPPH, which aims to determine antioxidant activity, and the disc diffusion method to determine antibacterial and antifungal activity. Carrot extract was obtained using the maceration method with a ratio of 1:10 using ethanol solvent 96% for the antioxidant test, while for the antibacterial and antifungal tests, acetone solvent was used. The extracted carrots yielded a yield of 10.1% (v/b). Based on the results of phytochemical screening, it is known that carrots contain flavonoids, saponins, tannins, and alkaloids, as well as functional groups indicating the presence of beta-carotene in carrots through FTIR. Carrots show weak antioxidant activity with an IC50 value of 125.944 ppm. The inhibitory activity of carrot extract during 24 hours of observation are concentration 40% (0.7 mm), 60% (0.77 mm) and 80% (0.85 mm). Meanwhile, in the antifungal test, carrot extract showed negative results at concentrations 60 and 80%, while at a concentration of 100% showed an inhibition zone of 0.835 mm.